Frontispiece: Freezing the Dynamic Gap for Selectivity: Motion‐Based Design of Inhibitors of the Shikimate Kinase Enzyme. Issue 50 (12th December 2016) - Prado, Verónica; Lence, Emilio; Thompson, Paul; Hawkins, Alastair R.; González‐Bello, Concepción
Abstract : Inhibitors Enzymes are "dynamic" systems that are able to adopt diverse conformations during catalysis—an open conformation (OFF) for product release and a closed form (ON) for substrate conversion. In their Full Paper onpage 17988 ff., C. González‐Bello et al. show how disabling the closure of the active site for catalysis is an alternative strategy for inhibitor design as well as for selectivity among homologous enzymes. They show that the incorporation of bulky groups at position C5 of 5‐aminoshikimic acid enhances the selectivity for shikimate kinase from Helicobacter pylori versus Mycobacterium tuberculosis due to key motion differences in the shikimic acid binding domain, which is highly conserved in the two bacterial enzymes.